ANALISIS IMPLEMENTASI AKAD IJARAH PADA MOTOR ELECTRIC PERUSAHAAN GRAB DI KOTA MEDAN - Hendra Setiawan; Rahmad Daim Harahap; Jamilah Ramadhan; Lismayanti; Puja My Lofenda; Rehulina Zuhra Ginting (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to analyze the ijarah system implemented by GrabBike drivers in Medan City related to the electric motorcycles used in their services. The research method used is a qualitative method conducted by direct observation, interviews with Grab drivers, and analysis of related documents. In Islam this economic system is referred to as ijarah, which means a contract of transfer of use rights to goods or services, through the payment of rent wages, without being followed by the transfer of ownership (ownership milkiyyah) of the goods themselves. The results showed that Grab has used the ijarah al-a'yan (muthlaqah) system as a rental method. In this ijarah system, the company rents electric motorbikes to drivers with a daily rental fee of Rp50,000.